2011
DOI: 10.3354/meps09229
|View full text |Cite
|
Sign up to set email alerts
|

South polar skuas from a single breeding population overwinter in different oceans though show similar migration patterns

Abstract: Seabirds in seasonal environments are often long-distance migrants and, for many species and populations, their ranges throughout the non-breeding period are unknown. As conditions during the non-breeding season often affect subsequent performance, the choice of migration strategy can have major implications for timing of breeding and success and, ultimately, population dynamics. We tracked south polar skuas Catharacta maccormicki from a single breeding population at King George Island in the South Shetland Is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
78
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 79 publications
(85 citation statements)
references
References 23 publications
(25 reference statements)
5
78
0
2
Order By: Relevance
“…2 & 3). Individual consistency in migration strategies was also recorded for 17 south polar skuas Catharacta maccormicki and 3 great skuas C. skua tracked in 2 and 3 consecutive nonbreeding seasons (Kopp et al 2011, Magnúsdóttir et al 2012, Weimerskirch et. al.…”
Section: Discussionmentioning
confidence: 99%
“…2 & 3). Individual consistency in migration strategies was also recorded for 17 south polar skuas Catharacta maccormicki and 3 great skuas C. skua tracked in 2 and 3 consecutive nonbreeding seasons (Kopp et al 2011, Magnúsdóttir et al 2012, Weimerskirch et. al.…”
Section: Discussionmentioning
confidence: 99%
“…Four main stopover areas were identified for Bugio petrels, located around the Cape Verde archipelago, the northeast coast of Brazil, northwest of the Azores and off the north coast of Brazil. Specific stopover sites, where birds are assumed to recover lost body condition, have been identified for most long -distance migratory seabirds in the Atlantic (Guilford et al 2009, Kopp et al 2011, Stenhouse et al 2012. Immersion data for some of these species, including Cory's shearwater and Manx shearwater Puffinus puffinus, indicate that like Bugio petrels, birds in stopover areas reduce flight speed and increase the proportion of time on the water (Guilford et al 2009.…”
Section: Non-breeding Distribution and Habitat Preferencesmentioning
confidence: 99%
“…The at-sea area used by Bugio petrels during this stage seems to overlap with the distribution of Zino's petrels Pterodroma madeira from Madeira (Zino et al 2011), Cory's shearwater Calonectris diometea from Desertas (Paiva et al 2010a) and Selvagens (Paiva et al 2010c), and Cape Verde shearwater Calonectris edwardsii from Cape Verde (Roscales et al 2011). The African shelf area along the coast of Mauritania appears to be very important for populations of these 4 seabird species for part or all of the year and also for migrant seabirds from elsewhere, including Sabine's gull Larus sabini (Kopp et al 2011), northern gannet Morus bassanus (Stenhouse et al 2012), great skua Stercorarius skua (Magnusdottir et al 2012) and south polar skua S. maccormicki (Fort et al 2012). In fact, this area is within one of the most important large marine ecosystems in the world -the Canary Current -with strong and nutrient-rich upwelling, which naturally elevates primary productivity and progressively increases the abundance of plankton and small planktivorous pelagic fish, cephalopods and crustaceans, which ultimately attracts seabirds to the area (Mann & Lazier 2006, Sherman & Hempel 2009).…”
Section: Habitat Use During the Breeding Stagementioning
confidence: 99%
“…Several studies have revealed the exceptional migratory performances of many seabirds Phillips et al 2005;Egevang et al 2010;Kopp et al 2011), in particular of shearwater species (e.g. Shaffer et al 2006;González-Solís et al 2007;Guilford et al 2009;Dias et al 2012a).…”
mentioning
confidence: 99%